2022
DOI: 10.1111/odi.14175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the periodontal viruses in cardiovascular patients associated with periodontitis

Abstract: Objectives The current study aimed in evaluating the prevalence of Epstein–Barr virus (EBV), cytomegalovirus (CMV), and herpes simplex virus (HSV) in periodontitis and/or coronary artery disease (CAD) patients to compare with their healthy controls and insist their significance in the same. Methodology Two hundred and forty patients were divided into 4 groups. Non‐periodontitis+non‐cardiac (NP+NC) = 60 patients, periodontitis+non‐cardiac patients (P+NC) = 60 patients, non‐periodontitis+cardiac patients (NP+C) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Previous studies have found that the composition of gut viruses is significantly changed in HTN and that gut viruses have a superior resolution and discrimination ability compared with bacteria in distinguishing healthy samples and hypertensive samples ( 22 ). Some studies have reported that the prevalence of Epstein‒Barr virus and cytomegalovirus is significantly higher in the subgingival plaques of PD patients, and the prevalence of viruses is the highest in PD patients with coronary artery disease ( 23 , 24 ). Overall, there is a lack of research on the role of the virome in HTN and PD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that the composition of gut viruses is significantly changed in HTN and that gut viruses have a superior resolution and discrimination ability compared with bacteria in distinguishing healthy samples and hypertensive samples ( 22 ). Some studies have reported that the prevalence of Epstein‒Barr virus and cytomegalovirus is significantly higher in the subgingival plaques of PD patients, and the prevalence of viruses is the highest in PD patients with coronary artery disease ( 23 , 24 ). Overall, there is a lack of research on the role of the virome in HTN and PD.…”
Section: Introductionmentioning
confidence: 99%